Rapid microwave-assisted synthesis of gold loaded hydroxyapatite collagen nano-bio materials for drug delivery and tissue engineering application. Issue 3 (15th February 2019) - Mondal, Sudip; Hoang, Giang; Manivasagan, Panchanathan; Moorthy, Madhappan Santha; Vy Phan, Thi Tuong; Kim, Hye Hyun; Nguyen, Thanh Phuoc; Oh, Junghwan
Abstract: A rapid microwave assisted facile synthetic technique was adopted to load gold nanoparticles (Au) on hydroxyapatite (HAp) surface. HAp nanoparticles were primarily synthesized by wet precipitation technique and further used for gold loading and successive collagen coating for biomedical applications. The microwave-assisted controlled synthesis technique with three heating cycles allows the very fast growing of Au seeds over HAp facets. Different sophisticated analytical techniques and spectroscopic characterization were employed to confirm the structural, chemical, and morphological features. The synthesized different concentration "Au" loaded hetero nanostructures coated with collagen (Au–HAp–Col) optimized for drug (Doxorubicin: DOX) loading and releasing purposes for biomedical applications. The maximum drug-loading efficiency of 58.22% and a pH responsive releasing of 53% (at pH 4.5) was obtained for 0.1 wt% Au–HAp–Col nanoparticles. To study the cytotoxic effects from the hetero nanostructures, MG-63 osteoblast-like cells were exposed to different concentration ranges on Au–HAp, Au–HAp–Col, and DOX loaded Au–HAp–Col nanoparticles. The non-toxic and bioactive properties of the synthesized nanoparticle-fabricated scaffold promotes cellular attachment, growth, and proliferation. These results indicated that optimized Au–HAp–Col nanoparticles may be promising drug delivery and scaffold materials for multifunctional biomedical applications.